2023
DOI: 10.3389/fmicb.2022.1090401
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of storage time on the silage quality and microbial community of mixed maize and faba bean in the Qinghai-Tibet Plateau

Abstract: Tibetan Plateau is facing serious shortage of forage in winter and spring season due to its special geographical location. Utilization of forages is useful to alleviate the forage shortage in winter and spring season. Consequently, the current study was aimed to evaluate the influence of storage time on the silage quality and microbial community of the maize (Zea mays L.) and faba bean (Vicia faba L.) mixed silage at Qinghai-Tibet Plateau. Maize and faba bean were ensiled with a fresh weight ratio of 7:3, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The current study further showed that including tannin extract as a silage additive modulated the microbial composition of the silage, favouring the dominance of phylum Firmicutes. These results agree with other studies that reported the dominancy of phylum Firmicutes on silage produced from different forage materials [41,[50][51][52][53][54]. Phylum Firmicutes constituted from 84% to 97% of the bacterium detected on maize silage in T2, T4, and T5, while in T1 and T3 maize silage, phylum Firmicutes constituted 39% and 42% of the detected bacteria, respectively.…”
Section: Silage Microbial Composition As Influenced By Additivessupporting
confidence: 91%
See 1 more Smart Citation
“…The current study further showed that including tannin extract as a silage additive modulated the microbial composition of the silage, favouring the dominance of phylum Firmicutes. These results agree with other studies that reported the dominancy of phylum Firmicutes on silage produced from different forage materials [41,[50][51][52][53][54]. Phylum Firmicutes constituted from 84% to 97% of the bacterium detected on maize silage in T2, T4, and T5, while in T1 and T3 maize silage, phylum Firmicutes constituted 39% and 42% of the detected bacteria, respectively.…”
Section: Silage Microbial Composition As Influenced By Additivessupporting
confidence: 91%
“…A low pH in silage indicates well-preserved silage and prevents undesirable bacterial growth [54]; this was observed in the current study, as all treatments recorded a pH below 4.0. However, the microbial characterisation of these silages using genomic technology analysis revealed the presence of undesirable bacteria in T1 (negative control) and T3 (positive control) silages.…”
Section: Silage Microbial Composition As Influenced By Additivessupporting
confidence: 73%
“…Lactococcus, a parthenogenetic anaerobic bacterium, is normally the most abundant in the early stages of silage when the growth and multiplication of Lactococcus are inhibited during the anaerobic process (Zeng et al, 2020). However, Acetobacter may promote the growth of Lactococcus (1.20-2.65%) and cause the proliferation of Sphingomonas, and the correlation between pH and Sphingomonas in the RDA was similar to that reported by Xin et al (2023). However, the abundance of Lactobacillus still significantly increased with the addition of fodder soybeans.…”
Section: Correlation Analysis Of the Silage Quality And The Microbial...supporting
confidence: 80%
“…As the proportion of mixed sowing of fodder soybeans increased, the abundance of Firmicutes gradually increased. The phylum Firmicutes ferments sugar into acid and inhibits Proteobacteria under anaerobic silage conditions, resulting in a decrease in its abundance (Xin et al, 2023). The dominant genera were Lactobacillus, Bradyrhizobium, Lactococcus, Sphingomonas, Klebsiella, and Pseudomonas.…”
Section: Effects Of the Different Mixed Sowing Ratios On The Bacteria...mentioning
confidence: 99%
“…Ensiling is an effective preservation method that can improve forage palatability, digestibility, and nutrient retention for long-term storage [6]. However, leaving corn stalks in the field, a common practice, leads to nutrient loss [7].…”
Section: Introductionmentioning
confidence: 99%